Physicochemical characterization and rheological properties of magnetic elastomers containing different shapes of corroded carbonyl iron particles - Nurul Liyana Burhannuddin (Nature Portfolio, 2021)
Abstract Carbonyl iron particles (CIPs) is one of the key components in magnetic rubber, known as magnetorheological elastomer (MRE). Apart from the influence of their sizes and concentrations, the role of the particle’ shape is pronounced worthy of the attention for the MRE performance. However, the usage of CIPs in MRE during long-term applications may lead to corrosion effects on the embedded CIPs, which significantly affects the performance of devices or systems utilizing MRE. Hence, the distinctions between the two types of MRE embedded in different shapes of spherical and plate-like CIPs, at both conditions of non-corroded and corroded CIPs were investigated in terms of the field-dependent rheological properties of MRE. The plate-like shape was produced from spherical CIPs through a milling process using a rotary ball mill. Then, both shapes of CIPs individually subjected to an accelerated corrosion test in diluted hydrochloric (HCl) at different concentrations, particularly at 0.5, 1.0, and 1.5 vol.% for 30 min of immersion time. Eight samples of CIPs, including non-corroded for both CIPs shapes, were characterized in terms of a morphological study by field emission scanning electron microscope (FESEM) and magnetic properties via vibrating sample magnetometer (VSM). The field-dependent rheological properties of MREs were analyzed the change in the dynamic modulus behavior of MREs via rheometer. From the application perspective, this finding may be useful for the system to be considered that provide an idea to prolong the performance MRE by utilizing the different shapes of CIPs even when the material is fading.